Analisis Faktor yang Mempengaruhi Minat Belajar Siswa Kelas XI IPS Pada Mata Pelajaran Geografi di SMA Negeri 1 Rasau Jaya - Hidayat, Topik; Sariani, Novita (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
This research aims to determine students' interest in learning in Geography lessons in class XI IPS SMA Negeri 1 Rasau Jaya. The research method used in this research is descriptive qualitative. The subjects in this research were the Geography teacher and 5 students in class XI IPS I SMA Negeri 1 Rasau Jaya. Data collection techniques use observation, interviews, and documentary studies, while data collection tools use observation sheets, teacher and student interview guides, and documentation. In the Geography learning process, there are factors that influence students' interest in learning. Interest is an interest in something so that we are moved to do that thing. Apart from that, interest is a psychological aspect that helps and encourages someone to fulfill their needs. There are two factors that influence students' interest in learning, namely internal and external factors. Internal factors include curiosity, motivation and physical factors. Meanwhile, external factors include family, school and community environment.